Causes of mortality and temporal patterns in breeding season survival of lesser prairie‐chickens in shinnery oak prairies. (9th June 2015) - Grisham, Blake A.; Boal, Clint W.
ABSTRACT Baseline survival and mortality data for lesser prairie‐chickens (Tympanuchus pallidicinctus) are lacking for shinnery oak (Quercus havardii) prairies. An understanding of the causes and timing of mortalities and breeding season survival in this ecoregion is important because shinnery oak prairies have hotter and drier environmental conditions, as well as different predator communities compared with the northern distribution of the species. The need for this information has become more pressing given the recent listing of the species as threatened under the U.S. Endangered Species Act. We investigated causes of mortality and survival of lesser prairie‐chickens during the 6‐month breeding season (1 Mar–31 Aug) of 2008–2011 on the Texas Southern High Plains, USA. We recorded 42 deaths of radiotagged individuals, and our results indicated female mortalities were proportionate among avian and mammalian predation and other causes of mortality but survival was constant throughout the 6‐month breeding season. Male mortalities were constant across avian and mammalian predation and other causes, but more mortalities occurred in June compared with other months. Male survival also varied by month, and survival probabilities were lower in June–August. We found predation on leks was rare, mortalities from fence collisions were rare, female survival did not decrease during incubation or brood‐rearing, and survival was influenced by drought. Our study corroborated recent studies that suggested lesser prairie‐chickens are living at the edge of their physiological tolerances to environmental conditions in shinnery oak prairies. As such, lesser prairie‐chickens in our study experienced different patterns of mortality and survival that we attributed to hot, dry conditions during the breeding season. Specifically, and converse to other studies on lesser prairie‐chicken survival and mortality, drought positively influenced female survival because females did not incubate eggs during drought conditions; the incubation period is when females are most vulnerable to predation. Male mortalities and survival were negatively influenced by drought later in the breeding season, which we attributed to rigorous lekking activities through late May combined with lack of food and cover as the breeding season progressed into summer. © 2015 The Wildlife Society.